2019
DOI: 10.1002/jssc.201900482
|View full text |Cite
|
Sign up to set email alerts
|

On‐line synergistic stacking in capillary zone electrophoresis featuring field‐amplified sample stacking and micelle to cyclodextrin stacking in the determination of two alkaloids in complicated matrix samples

Abstract: A novel on‐line synergistic proconcentration strategy coupling field‐amplified sample stacking and micelle to cyclodextrin stacking for cationic analytes in capillary zone electrophoresis has been proposed and applied for the separation and determination of two alkaloids, matrine, and oxymatrine in complicated matrix samples. The approach was performed by the long injection of sample in a low‐conductivity sodium dodecyl benzene sulfonate solution followed by the injection of hydroxypropyl‐β‐cyclodextrin soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…This was due to the higher buffer concentration contributing to a bigger conductivity difference between the sample and BGE, which is favorable to an enrichment effect. However, more Joule heating was also generated owing to the high concentration of electrolyte (50 m m ), leading to a decrease in signal sensitivity and enrichment of analytes (C. Chu et al, 2019). Thus, 45 m m of NaH 2 PO 4 in BGE was used in the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the higher buffer concentration contributing to a bigger conductivity difference between the sample and BGE, which is favorable to an enrichment effect. However, more Joule heating was also generated owing to the high concentration of electrolyte (50 m m ), leading to a decrease in signal sensitivity and enrichment of analytes (C. Chu et al, 2019). Thus, 45 m m of NaH 2 PO 4 in BGE was used in the subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the peak area of 5‐FU increased as the SDS concentration increased from 10 to 50 m m , and then dropped at 60 m m of SDS (Figure 3c). This was expected because high concentration of SDS could result in strong interaction between micelle and analytes, which increased the difficulty of reversing the effective electrophoretic mobility and thereby caused the suppression of signal sensitivity (C. Chu et al, 2019). The peak area did not further increase at SDS concentration >50 m m ; thus, 50 m m was used for further optimization.…”
Section: Resultsmentioning
confidence: 99%
“…A templating agent that is analogous to a surfactant is stacked CD. With its characteristic open pore channels when stacked (The CD structure is one of a truncated cone), it has been shown to be well-suited to separation methods [70]. For pore formation in sol-gel films on electrodes, it overlaps EASA in terms of size domain [22,26], but unlike a surfactant, CD does not influence the structure or strength of the bulk portion of the silica film [28,71].…”
Section: Applications Of Sol-gel Modified Electrodesmentioning
confidence: 99%
“…Recently, dual or multiple focusing techniques were explored as alternatives for further improving the detection sensitivity. Some of these techniques are ITP‐stacking [22], field‐amplified sample stacking‐moving reaction boundary [23], field‐amplified sample stacking‐micelle to cyclodextrin stacking [24], and ionic liquid micelle based three‐step stacking [25].…”
Section: Introductionmentioning
confidence: 99%